2011
DOI: 10.1164/rccm.201005-0792oc
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of p38 and MKP-1 in Response to NOD1/TLR4 Stimulation in Sarcoid Bronchoalveolar Cells

Abstract: Rationale: Sarcoidosis is a systemic inflammatory disorder characterized by distinct up-regulation of Th1 cytokines, such as tumor necrosis factor (TNF)-a and IL-12. The mechanism underlying this up-regulation remains unclear. Recognition of microbial moieties through Toll-like or Nod-like receptors evokes sequential activation of mitogen-activated protein kinases (MAPKs), which plays a role in Th1-immune response. Objectives: To test the hypothesis that dysregulation in MAPK signaling in response to microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 51 publications
7
83
0
1
Order By: Relevance
“…Stimulation of the nucleotidebinding oligomerization domain 1 (NOD1) results in enhanced expression of TNF and IL12/IL23 p40 in a subset of sarcoidosis patients [43]. Of interest, mutations in the NOD2 gene are strongly associated with a clinical triad of joint, eye, and skin involvement observed in a subset of pediatric sarcoidosis cases [44], although this linkage does not appear to Genetic-environmental interactions • Heightened risk for extra-pulmonary disease associated with exposures (insecticide, molds, and musty odors) in HLA-DRB1*1101 patients be present in adult sarcoidosis [45][46][47][48].…”
Section: Genetic and Immunologic Interactions In Sarcoidosis Etiologymentioning
confidence: 99%
“…Stimulation of the nucleotidebinding oligomerization domain 1 (NOD1) results in enhanced expression of TNF and IL12/IL23 p40 in a subset of sarcoidosis patients [43]. Of interest, mutations in the NOD2 gene are strongly associated with a clinical triad of joint, eye, and skin involvement observed in a subset of pediatric sarcoidosis cases [44], although this linkage does not appear to Genetic-environmental interactions • Heightened risk for extra-pulmonary disease associated with exposures (insecticide, molds, and musty odors) in HLA-DRB1*1101 patients be present in adult sarcoidosis [45][46][47][48].…”
Section: Genetic and Immunologic Interactions In Sarcoidosis Etiologymentioning
confidence: 99%
“…Conflicting results have been obtained for TLR4 gene variants in Caucasian and Japanese cohorts [107,108], which point to a causative variation in the vicinity of the TLR4 gene [109]. Nevertheless, an increased expression of TLR2, TLR4, and TLR9 and their signal transduction is observed in sarcoidosis [110][111][112]. TLRs are members of the pattern recognition receptors involved in microbial defence.…”
Section: Geneticsmentioning
confidence: 99%
“…Thus, in susceptible individuals, inanimate remnants of bacteria or remote infection may be capable of inducing sustained sarcoid-like inflammation (51,52). The nature of these disease susceptibilities may be queried in genome-wide association studies, which have identified a number of gene variants associated with sarcoidosis and other granulomatous disorders (53)(54)(55).…”
Section: Other Dplds Sarcoidosismentioning
confidence: 99%